Alfa-beta transformation approach for the active shielding of flat power line - Grinchenko, V.S. (Технічна електродинаміка, 2014)
This paper deals with the active shielding of the magnetic field of a flat three-phase power line. The present study considers active loops with the magnetic moment opposite to the magnetic moment of the β-component currents circuit, arising in alpha-beta transformation applied to three-phase power line currents. Relationship between the size of the proposed active loops and the electric current is derived. Presented results show that such active loops allow reduction of the width of sanitary-hygienic zone under power lines, where the magnetic flux density exceeds the reference level, by 11% compared to the known active loops. В статье рассмотрено снижение магнитного поля трехфазной линии электропередачи с горизонтальным расположением фаз при помощи активного контурного экрана. Расположение, размеры и ток активного контурного экрана определяются таким образом, чтобы его магнитный момент был противоположен магнитному моменту контура тока β-компоненты, возникающей при альфа-бета преобразовании токов трехфазной линии электропередачи. Установлено, что такой экран позволяет уменьшить на 11% ширину
санитарно-защитной зоны, в которой уровень магнитной индукции ЛЭП превышает гранично-допустимый, по сравнению с контурными экранами, известными из литературных источников У статті розглянуто зниження магнітного поля трифазної лінії електропередачі з горизонтальним розташуванням фаз за допомогою активного контурного екрана. Розташування, розміри та струм активного контурного екрану визначаються таким чином, щоб його магнітний момент був протилежний магнітному моменту контуру струму β-компоненти, що виникає при альфа-бета перетворенні струмів трифазної лінії електропередачі. Встановлено, що такий екран дозволяє зменшити на 11 % ширину санітарно-захисної зони, в якій рівень магнітної індукції ЛЕП перевищує гранично-припустимий, в порівнянні з контурними екранами, відомими з літературних джерел.